Human neuromuscular junction three-dimensional organoid models and the insight in motor disorders. (16th July 2021) - Zhang, Kejing; Bai, Lei; Xu, Wentao; Shen, Chengyong
Abstract: The neuromuscular junction (NMJ), a peripheral synaptic connection between motoneurons and skeletal muscle fibers, controls movement. Dysregulation of NMJs has been implicated in various motor disorders. Because of their large size and easy accessibility, NMJs have been extensively investigated in the neuroscience field and have greatly contributed to our understanding of the fundamental principles of synapses in the central nervous system. Researchers have tried multiple ways to develop models to recreate NMJs. Rapid progress in the research and development of tissue-like organoids has made it possible to produce human NMJ three-dimensional (3D) models in vitro, providing an additional powerful strategy to study NMJs. Here, we introduce the most recent advances of human embryonic stem cell- or induced pluripotent stem cell-derived organoids to model 3D NMJs.